High-Isolated MIMO Antenna Design Based on Pattern Diversity for 5G Mobile Terminals - Xu, Zhan; Deng, Changjiang (IEEE antennas and wireless propagation letters, 2020)
In this letter, a novel multiple-input-multiple-output (MIMO) antenna operating at 3500 MHz band is presented for 5G mobile terminals. The proposed antenna includes four blocks. Each block consists of two face-to-face elements with total size of 25 × 3.5 mm 2 . Rather than excited separately, the two elements are excited simultaneously. Pattern diversity is achieved by using in-phase and out-of-phase signals. A compact two-port feed network is designed to provide the required feed signals. The measured bandwidth for the two ports is 750 MHz (3.06-3.81 GHz) and 340 MHz (3.33-3.67 GHz), which is sufficient to cover the 3400-3600 MHz band. The port isolation is higher than 14 dB in the overlapping bandwidth.